Use inquiry forms effectively to boost recruitment efforts. Issue 2 (31st October 2019) - Hope, Joan
Abstract : TORONTO — Recruiting students to graduate programs is a challenging business. The Trump administration has made it even more difficult with its travel bans and visa restrictions, said Robert Ruiz, Vice President for Strategic Enrollment at Liaison.